Criminal Policy on Destructive Fishing Activities in Serutbar, Indonesia - Lewerissa, Yanti Amelia; Hehanussa, Deassy Antoneta; Adam, Sherly (Universitas Negeri Gorontalo, 2023)
Fishing communities around the North Seram and North West Seran (Serutbar) Marine Protected Areas often carry out destructive fishing activities. This study aimed to examine and analyze criminal policies for destructive fishing activities in the Serutbar Marine Conservation Area. The research method used is normative legal research supplemented by a socio-legal approach. The approach used in this study is a statutory approach and a conceptual approach. The data collection technique is a literature study complemented by field data obtained through observation and in-depth stakeholder interviews. Furthermore, the data were analyzed qualitatively. Based on the research results, Gale-Gale Village and Sawai Village's fishing communities around the Serutbar Waters Conservation Area often carry out destructive fishing activities. The factors that cause them to carry out destructive fishing are economic needs; very simple fishing gear; the provision of assistance needs to be put on target; Pokmaswas being less empowered; and a lack of inter-agency oversight. Meanwhile, countermeasures to overcome destructive fishing can be carried out through penal and non-penal approaches. And a need for inter-agency oversight. Meanwhile, countermeasures to overcome destructive fishing can be carried out through penal and non-penal approaches. And a need for inter-agency oversight. Meanwhile, countermeasures to overcome destructive fishing can be carried out through penal and non-penal approaches.